Exploring a digital ecosystem conceptual model and its simulation prototype - Wu, Chen; Chang, Elizabeth (Institute of Electrical and Electronics Engineers (IEEE), 2007)
Digital ecosystems (DES) transcend the traditional rigorously defined collaborative environments from centralised or distributed or hybrid models into an open, flexible, domain cluster, demand-driven interactive environment. A digital ecosystem is new-networked architecture and collaborative environment that addresses the weakness of client-server, peer-to- peer and Web services. In this paper, we firstly introduce a conceptual model of DES. The design and implementation of a DES simulation is then presented to illustrate some fundamental characteristics for further DES study. Finally, we propose a novel approach to realise the DES built on top of the social software (SS) and swarm intelligence.